Macromarketing Pedagogy: Empowering Students to Achieve a Sustainable World. (March 2021) - Shapiro, Stanley; Beninger, Stefanie; Domegan, Christine; Reppel, Alexander; Stanton, Julie; Watson, Forrest
The United Nation's Sustainable Development Goals (SDGs) are challenging the world to work towards a more sustainable future. Its 17 goals are ambitious, requiring concerted and system-based efforts driven by critical and socially aware thinking. However, marketing education is largely falling short of teaching students to think that way. Given macromarketing's unique perspective on the interactions among markets, marketing, and society, macromarketers are poised to contribute to marketing pedagogy and to commit students to realizing the SDGs. This article first looks back at the previous 40 years of macromarketing pedagogy, before offering contemporary approaches to teaching macromarketing through four illustrative case studies found in an online repository called Pedagogy Place. It then looks forward, setting an aspiring vision for macro-oriented classrooms in the coming years.